How can computer-based methods help researchers to investigate news values in large datasets? A corpus linguistic study of the construction of newsworthiness in the reporting on Hurricane Katrina. (April 2015) - Potts, Amanda; Bednarek, Monika; Caple, Helen
This article uses a 36-million word corpus of news reporting on Hurricane Katrina in the United States to explore how computer-based methods can help researchers to investigate the construction of newsworthiness. It makes use of Bednarek and Caple's discursive approach to the analysis of news values, and is both exploratory and evaluative in nature. One aim is to test and evaluate the integration of corpus techniques in applying discursive news values analysis (DNVA). We employ and evaluate corpus techniques that have not been tested previously in relation to the large-scale analysis of news values. These techniques include tagged lemma frequencies, collocation, key part-of-speech tags (POStags) and key semantic tags. A secondary aim is to gain insights into how a specific happening – Hurricane Katrina – was linguistically constructed as newsworthy in major American news media outlets, thus also making a contribution to ecolinguistics.